Zinc Oxide Nanostructures: Synthesis and Characterization - Sotirios Baskoutas (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
The summary should be ca. 200 words; this text will present the book in all promotional forms (e.g. flyers). Please describe the book in straightforward and consumer-friendly terms. [Zinc oxide (ZnO) is a wide band gap semiconductor with an energy gap of 3.37 eV at room temperature. It has been used considerably for its catalytic, electrical, optoelectronic, and photochemical properties. ZnO nanomaterials, such as quantum dots, nanorods, and nanowires, have been intensively investigated for their important properties. Many methods have been described in the literature for the production of ZnO nanostructures, such as laser ablation, hydrothermal methods, electrochemical deposition, sol-gel methods, chemical vapour deposition, molecular beam epitaxy, the common thermal evaporation method, and the soft chemical solution method. The present Special Issue is devoted to the synthesis and characterization of ZnO nanostructures with novel technological applications.]